KEPUTUSAN PENGGUNAAN APLIKASI OVO YANG DI PENGARUHI OLEH E-WOM DENGAN KEPERCAYAAN SEBAGAI VARIABEL MEDIASI PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS RIAU - Rahmi Yanti; Gatot Wijayanto; Deny Setiawan (Universitas Nusa Cendana, 2023)
This study is to investigate the direct and indirect effects regarding the Decision to Use the OVO application which is influenced by e-WOM with Trust as a mediating variable. This study is applied to the user of OVO application at the University of Riau, especially undergraduate students in the Faculty of Economics and Business. Determination of the sample in this study using Isaac and Michael's table from a certain population with a level of 5% as many as 251 respondents. The results of this study indicate that e-WOM can increase the level of Trust in the use of OVO applications. e-WOM strengthened the Decision to Use, Trust can mediate the effect of e-WOM in improving the Decision to Use. Keywords: e-WOM; Trust; Decision to use